2023
DOI: 10.1186/s12889-023-15274-x
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic differences in social determinants of health and health outcomes among adolescents and youth ages 10–24 years old: a scoping review

Abstract: Introduction With the recent emergence of the Healthy People 2030 goals there is a need to understand the role of SDOH on health inequalities from an upstream perspective. This review summarizes the recent body of evidence on the impact of SDOH across adolescence and youth health outcomes by race/ethnicity using the Health People 2030 Framework. Methods A systematic, reproducible search was performed using PubMed, Academic Search Premier, PsychInfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Disaggregated data were most commonly available for age, sex, geography, deprivation, and urbanization, but inequality patterns among other important dimensions (e.g., disability, race and ethnicity, sexual orientation) were very limited. The scarcity of data on drivers of health such as race or ethnicity and sexual orientation is a significant evidence gap as these factors are known to impact health outcomes and access to healthcare [ 42 , 43 ]. Furthermore, despite ample reporting on sex and gender, the absence of clear definitions, lack of transparency on how these data were collected, and their reporting as binary variables could potentially mean that sex and gender were being used interchangeably and were therefore conflated [ 44 – 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Disaggregated data were most commonly available for age, sex, geography, deprivation, and urbanization, but inequality patterns among other important dimensions (e.g., disability, race and ethnicity, sexual orientation) were very limited. The scarcity of data on drivers of health such as race or ethnicity and sexual orientation is a significant evidence gap as these factors are known to impact health outcomes and access to healthcare [ 42 , 43 ]. Furthermore, despite ample reporting on sex and gender, the absence of clear definitions, lack of transparency on how these data were collected, and their reporting as binary variables could potentially mean that sex and gender were being used interchangeably and were therefore conflated [ 44 – 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are similar to those from a cross-sectional study by Ogden et al 24 that demonstrated differing associations between obesity and household income among youth across race and ethnicity groups, with high household income associated with lower obesity prevalence among Asian and Hispanic youths, but no income-related difference among White and Black youths. Similarly, a scoping review of associations between SDOH and health risk behaviors (eg, substance use, high-risk sexual behavior) among adolescents and young adults aged 10 to 24 years 25 found that associations differed across racial and ethnic groups and by SDOH assessed. These findings underscore the complexity of the associations among racial and ethnic identity, exposure to adverse SDOH, and health outcomes in youths.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a scoping review of associations between SDOH and health risk behaviors (eg, substance use, high-risk sexual behavior) among adolescents and young adults aged 10 to 24 years 25 found that associations differed across racial and ethnic groups and by SDOH assessed. These findings underscore the complexity of the associations among racial and ethnic identity, exposure to adverse SDOH, and health outcomes in youths.…”
Section: Discussionmentioning
confidence: 99%
“… 19 These multifaceted changes in quality of life may be affected by social determinants of health and family contextual factors. 20 , 21 Additionally, racial disparities exist in pediatric ED outcomes, including appendicitis care, diagnostic imaging, antibiotic usage, gastroenteritis, and pain management. 22 26 These known racial disparities in emergency care and outcomes suggest that there may be racial disparities in other important measures, including caregiver QoL.…”
Section: Introductionmentioning
confidence: 99%